Mdm2 Phosphorylation Regulates Its Stability and Has Contrasting Effects on Oncogene and Radiation-Induced Tumorigenesis - Michael I. Carr; Justine E. Roderick; Hugh S. Gannon; Michelle A. Kelliher; Stephen N. Jones (Cell Reports, 2016)
ATM phosphorylation of Mdm2-S394 is required for robust p53 stabilization and activation in DNA-damaged cells. We have now utilized Mdm2S394A knockin mice to determine that phosphorylation of Mdm2-S394 regulates p53 activity and the DNA damage response in lymphatic tissues in vivo by modulating Mdm2 stability. Mdm2-S394 phosphorylation delays lymphomagenesis in Eμ-myc transgenic mice, and preventing Mdm2-S394 phosphorylation obviates the need for p53 mutation in Myc-driven tumorigenesis. However, irradiated Mdm2S394A mice also have increased hematopoietic stem and progenitor cell functions, and we observed decreased lymphomagenesis in sub-lethally irradiated Mdm2S394A mice. These findings document contrasting effects of ATM-Mdm2 signaling on p53 tumor suppression and reveal that destabilizing Mdm2 by promoting its phosphorylation by ATM would be effective in treating oncogene-induced malignancies, while inhibiting Mdm2-S394 phosphorylation during radiation exposure or chemotherapy would ameliorate bone marrow failure and prevent the development of secondary hematological malignancies.